2011
DOI: 10.1097/iae.0b013e318203c183
|View full text |Cite
|
Sign up to set email alerts
|

Endophthalmitis After Pars Plana Vitrectomy

Abstract: Small-gauge transconjunctival PPV does not appear to increase the rates of post-PPV endophthalmitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 23 publications
1
27
2
1
Order By: Relevance
“…Earlier research found that rates were increased in smaller-gauge surgery [30]. However, more recent and larger studies have found no significant difference in the rate of endophthalmitis with smaller-gauge surgery [31,32]. It is likely that these differing conclusions reflect the evolution of small-gauge surgery: improving surgical technique and advancing technology have perhaps resulted in a decreasing incidence of endophthalmitis.…”
Section: Discussionmentioning
confidence: 65%
“…Earlier research found that rates were increased in smaller-gauge surgery [30]. However, more recent and larger studies have found no significant difference in the rate of endophthalmitis with smaller-gauge surgery [31,32]. It is likely that these differing conclusions reflect the evolution of small-gauge surgery: improving surgical technique and advancing technology have perhaps resulted in a decreasing incidence of endophthalmitis.…”
Section: Discussionmentioning
confidence: 65%
“…Beveled incisions and newer vitrectomy systems have been introduced in an attempt to reduce the risk of postoperative hypotony and related complications. These have lowered the risk of hypotony, and may account for recent reports that small incision postoperative endophthalmitis rates are currently low (0.02%) and comparable with endophthalmitis rates following 20-gauge vitrectomy 911. However, hypotony remains a frequent complication following 25-gauge vitrectomy surgery.…”
Section: Introductionmentioning
confidence: 94%
“…Initially, narrow-gauge vitrectomy was thought to be associated with a higher incidence of endophthalmitis than 20-gauge PPV; however, this has not proven to be true. 148, 149 …”
Section: Treatment Optionsmentioning
confidence: 99%